Improving Reading Comprehension Through Think-Pair-Share (TPS) Technique Students of STIK Siti Khadijah Palembang - nyayu suryani; Abdul Aziz Rifa’at (Universitas Lancang Kuning, 2019)
The objectives of this study were to find out : (1) the significant improvement on the third semester students’ reading comprehension before and after being taught using Think-Pair-Share technique at STIK Siti Khadijah Palembang, South Sumatera, Indonesia; and (2) the significant difference on students’ reading comprehension between the students who were taught by using Think-Pair-Share technique and those who were not. The population of this study was all the third semester students of STIK Siti Khadijah Palembang which consist of 56 students in academic year 2018/2019. The sample of this study was taken by using total sampling. Thus, the total number of the sample was 56 students. The sample was the third semester students at D.III Nursing Study Program (experimental group) which consist of 28 students and the third semester students at S1 Nursing Study Program (control group) which consist of 28 students. The test was given twice to both experimental and control group. True experimental design was used to analyzed the data. To verify the hypotheses, the data used only posttest design to analyzed by using paired sample t-test and independent sample t-test was 0.005 which was lower than 0.05.The result of this study showed that Reading Comprehension by using Think-Pair-Share technique gave significant improvement on the students’ reading comprehension and gave significant difference between students’ who were taught by Think-Pair-Share technique and those who were not.